Calibration of chlorophyll hand-held meter based on vineyard NDVI zones for estimation of leaf N content - da Silva, Thassio Monteiro Menezes [UNESP]; Costa, Bruno Ricardo Silva [UNESP]; Oldoni, Henrique [UNESP]; Mitsuyuki, Milene Corso; Bassoi, Luís Henrique (FapUNIFESP (SciELO), 2022)
The monitoring of chlorophyll content in grapevine leaves allows us to evaluate their N status, assisting with the information for the decision make about nutrient rate and application time to the vineyard. The present work aimed to propose an easy-to-use procedure for the calibration of a chlorophyll hand-held meter based on the NDVI homogeneous zones in a vineyard for the device readings and leaf sampling. We evaluated the wine grape ‘Chardonnay’ growing under drip irrigation in a vineyard located in the Southeast region of Brazil. Readings of the relative chlorophyll indices (a, b, and total) were taken in situ four times throughout the 2019 growing season, with the device placed on two leaves of every 40 pre-selected target plants in two homogeneous zones of NDVI previously defined in the vineyard. Subsequently, the chlorophyll and leaf nitrogen contents were determined in laboratory to relate them to the chlorophyll meter readings through generalized estimation equations. The chlorophyll meter is capable of estimating the levels of chlorophyll a, b and total by the models generated with an error of 0.98, 0.58, and 1.47 µg ml-1 cm-2 for calibration and of 1.03, 0.67, and 1.49 µg ml-1 cm-2 for prediction, respectively. The functions developed for the leaf N content present calibration error of 1.49 g kg-1 and prediction error of 3.39 g kg-1, but capable of providing an estimate when error is less than the amplitude of nitrogen sufficiency.
Calibração do medidor portátil de clorofila com base em zonas de NDVI do vinhedo para a estimativa do contéudo de N na folha
Keywords: drip irrigation; precision viticulture; Vitis vinifera L.; wine grapevine